2020
DOI: 10.1111/bcp.14535
|View full text |Cite
|
Sign up to set email alerts
|

Prescriber compliance to direct oral anticoagulant labels and impact on outcomes in Thailand

Abstract: Aims This study aimed to evaluate the prescriber compliance to the approved labels of direct oral anticoagulants (DOACs) and impact of appropriateness of dosing on clinical outcomes. Methods A retrospective study was conducted using simple‐stratified random sampling of adult patients receiving ≥6 months of DOACs for various indications during 2013–2017 in 10 tertiary care hospitals. Patients were classified into 3 dosing groups including approved dose, underdosing and overdosing based on the Thai Food and Drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…We used data from the recent study by Wattanaruengchai et al for which the original design and the results of the main study have been published previously 17 . Briefly, the study was a multicentre study conducted in 10 public, tertiary care hospitals from four provinces (Bangkok, Chiang Mai, Nakhon Nayok and Nakhon Ratchasima) in Thailand to evaluate the appropriateness of DOAC use in mixed indications.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used data from the recent study by Wattanaruengchai et al for which the original design and the results of the main study have been published previously 17 . Briefly, the study was a multicentre study conducted in 10 public, tertiary care hospitals from four provinces (Bangkok, Chiang Mai, Nakhon Nayok and Nakhon Ratchasima) in Thailand to evaluate the appropriateness of DOAC use in mixed indications.…”
Section: Methodsmentioning
confidence: 99%
“…Risk was classified into two levels for low‐ (score 0‐2) and high‐ (score ≥3) risk groups. For the evaluation of DOAC, the labile INR criteria of HAS‐BLED was set to 0 in all patients except those receiving an overdose of DOAC, where it was set to 1, given that inappropriate DOAC overdosing has been shown to increase the risk of bleeding 17 . The ORBIT bleeding risk score comprises five risk factors: age ≥75, anaemia, bleeding history, estimated glomerular filtration rate (eGFR) of <60 mL/min/1.73 m 2 (calculated by the modification of diet in renal disease equation) and use of antiplatelet drugs 11 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although prescribers may have valid reasons for using off-label DOACs, no studies have yet demonstrated an association between this practice and improved outcomes. Some studies have documented an association between off-label use and increased risk of adverse events, [ 12 , 13 ] but others have not [ 9 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%